USE OF A SPECIAL SPLINT IN REVERSE SURAL ARTERY FLAP TO REDUCE VENOUS CONGESTION AND FLAP NECROSIS - Masood, Tariq; Ahmed, Riaz; ., Obaidullah (Journal of Ayub Medical College Abbottabad, 2016)
Background: Distally based sural fascio-cutaneous flap is a commonly performed plastic surgery procedure for the coverage of distal third of leg, ankle and foot defects. However congestion is the main complication of this flap which results into partial or complete loss of the flap. We devised a special splint to reduce this complication and retrospectively reviewed its effect on this complication between two groups. Methods: This retrospective study was carried out at Northwest General hospital between 1995 and 2012. Group-A included 30 patients who were managed without the splint between 1995 and 2005 and group B comprised of 35 patients were treated with the splint between 2006 and 2012. Complications like venous congestion, epidermolysis, and partial and complete flap failure were documented. Data were analyzed by SPSS.16.5 software. Chi- square test was used for data analysis. P value less than 0.05 was considered as the level of significance. Results: Total 65 patients were operated. Age of the patients ranged from 7 to 60 years. Road traffic accident and spoke wheel injury was the main cause of soft tissue loss in our patients. In group A 12 patients suffered from venous congestion. Out of 12, three patients had epidermolysis while partial flap necrosis occurred in 9 patients. Only 3 patients had venous congestion in group B. Two patients suffered from epidermolysis and one had partial flap necrosis. None of patient suffered from complete flap loss in both groups. Conclusion: Reverse sural artery flap continues to be a versatile flap for distal lower extremity reconstruction. By using a special splint to reduce pressure on the pedicle site as a modification, flap complication rate can be decreased significantly.